Credit constrained R&D spending and technological change - Pascal Aßmuth (Bielefeld University, Center for Mathematical Economics (IMW), 2014)
Firms often rely on external financing in order to conduct R&D. The question is to what extend discriminatory behaviour of the funds provider affects the industry evolution. The model is based on an evolutionary framework by Nelson and Winter. A firm chooses its R&D spending in an adaptive fashion where technological improvement is essential for survival in the competitive market. Firms can finance their activities by using retained profits or applying for credit. However, they have a clear hierarchy in choosing the source of funds and saved profits are always used up first. There is endogenous discriminatory lending as the banking sector provides credit according the firms' individual features. It compares profitability and market share across firms when assessing creditworthiness. The model is able to capture features of innovation and diffusion of technology. Results show that the availability of credit is crucial for technological change in a non-linear fashion and that the industry evolves faster if the bank values market share more in assessing creditworthiness.
urn:nbn:de:0070-pub-27591315
Keywords: D92; G32; O33; O41; 330; Heterogeneous Agents Models; Innovation; Financial Constraints